Analisis Semiotika Roland Barthes Representasi Kekuasaan dalam Komunikasi Raja pada Film The King’s Speech - Achmad Zaidan Zaahir; Muhammad Jailani (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Film as a medium of mass communication not only serves as entertainment but also reflects social realities, including the construction of power. In The King's Speech (2010), King George VI's authority is represented through communication practices despite his speech impediment. This study examines how symbolic power is represented in the film and how communicative vulnerability is transformed into leadership legitimacy. Using a qualitative method and Roland Barthes' semiotic framework, the analysis explores denotative, connotative, and mythological meanings in selected scenes, dialogues, expressions, gestures, and visual elements. The findings show that symbolic power is constructed through four key communicative scenes. At the denotative level, the film portrays the king's struggle to overcome stammering. At the connotative level, vulnerability becomes a space for negotiating authority and rebuilding legitimacy. At the mythological level, the film promotes the idea that modern leadership is grounded not only in hereditary status but also in communicative competence, resilience, and public recognition. The study's novelty lies in demonstrating that symbolic power emerges paradoxically from communicative fragility, transforming speech impairment into a performative source of modern political legitimacy.